2018
DOI: 10.1371/journal.pone.0199745
|View full text |Cite
|
Sign up to set email alerts
|

Disparities by race, age, and sex in the improvement of survival for lymphoma: Findings from a population-based study

Abstract: ObjectiveTo evaluate improvement in survival of lymphoma patients from 1990 to 2014, stratified by age, sex and race using Surveillance Epidemiology and End-Result Survey Program (SEER) data.Study design and settingWe identified 113,788 incident lymphoma cases from nine SEER cancer registries were followed up for cause-specific mortality from lymphoma. Cox proportional hazard regression was used to estimate hazard ratios (HRs) and their respective 95% confidence interval (CIs) for various time periods within g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
1
9
0
1
Order By: Relevance
“…The SEs of OSP‐based estimators are smaller than those of UNIF. The effects of age and gender are positive, which agree with the findings in Mukhtar et al 18 Moreover, it seems that age (θ1) is a significant risk factor. To further check the rationality of our method, we give bias, ESE and SSE of the subsample‐based estimates based on 1000 subsamples in Table 6, where r = 200, 400, and 600, respectively.…”
Section: A Real Data Examplesupporting
confidence: 91%
“…The SEs of OSP‐based estimators are smaller than those of UNIF. The effects of age and gender are positive, which agree with the findings in Mukhtar et al 18 Moreover, it seems that age (θ1) is a significant risk factor. To further check the rationality of our method, we give bias, ESE and SSE of the subsample‐based estimates based on 1000 subsamples in Table 6, where r = 200, 400, and 600, respectively.…”
Section: A Real Data Examplesupporting
confidence: 91%
“…We constructed approximate 10-year time periods to minimize small sample bias in our sub-group analysis. We assessed for interactions of the year of diagnosis with race/ethnicity, age and sex, respectively, for each of the four categories of leukemia using likelihood ratio tests [17,18], following similar strategy in our prior works [19,20], in which race/ethnicity, age or sex were included in multivariate models as covariates when they were not involved with interactions alongside marital status and cancer registry site.…”
Section: Methodsmentioning
confidence: 99%
“…Poorer survival in the oldest old patients with cancer in part reflects the numerous challenges with cancer treatment in this population, as previously discussed. However, studies also suggest that older patients have benefited less than younger patients from recent advances in cancer therapeutics, whether because of lower efficacy or use of ineffective doses . One study found that smaller improvements in survival for older versus younger patients with cancer from 1990 to 2009 for 6 leading cancers led to widening age‐related disparities .…”
Section: Selected Findingsmentioning
confidence: 99%
“…However, studies also suggest that older patients have benefited less than younger patients from recent advances in cancer therapeutics, whether because of lower efficacy or use of ineffective doses. 94,95 One study found that smaller improvements in survival for older versus younger patients with cancer from 1990 to 2009 for 6 leading cancers led to widening agerelated disparities. 95 Balancing the risks of undertreatment versus overtreatment is critical for older patients who have cancer.…”
Section: Cancer Survivalmentioning
confidence: 99%